Web-Based Financial Information System in The Christian Evangelical Church in Minahasa - Salaki Reynaldo Joshua; Heilbert Armando Mapaly; Kenneth Yosua Palilingan (Lembaga Pengembangan Kinerja Dosen, 2023)
As a community service organization, the church has a variety of activities and transactions to meet the needs of the congregation. Because the church has quite complex business processes and systems, information, including data storage, is required to facilitate an integrated and centralized church in data storage, management, and presentation. The analysis, design, and construction of a church financial information system as a solution to the problems that exist in the GMIM church, where processing will be maximized in a web-based financial information system, are discussed in this study.